Hypertension across the lifespan: Older adults. Issue 4 (July 2021) - Hilliard, Tara C.; Bruce, Kellie; Esquibel, Karen A.; Mello, Inola; Moore, Amy
Abstract : Effective diagnosis and management in the older adult population can increase functional capacity and decrease morbidity and mortality. Abstract : Effective diagnosis and management in the older adult population can increase functional capacity and decrease morbidity and mortality.